PREVIOUS IMPLEMENTATION OF WOMEN'S EMPOWERMENT BY PKK CADRE IN BINGKENG VILLAGE DAYEUHLUHUR DISTRICT CILACAP REGENCY - Fitria Handayani; Kiki Endah; Neti Sunarti (JGSRD: Journal of Government Science and Rural Development, 2020)
In Indonesia, poverty is increasing from year to year, especially women who have become housewives. The implementation of empowerment for underprivileged women held by PKK cadres is an effort that aims to improve the welfare of women, especially in the economic sector. There are three indicators of the problem, namely the socialization which is carried out ineffective so that it is less attractive to women. For example, socialization only involves community leaders such as the head of the RT, the head of the RW, and the head of the hamlet because there are insufficient funds. The lack of knowledge and insight of underprivileged women about the importance of empowerment so that underprivileged women do not take this empowerment seriously and optimally. For example: when the coaching was carried out, only a small proportion of pre-prosperous women attended the training at the Village Hall. Time management is not optimal, causing short coaching time. Example: coaching is carried out for 3 hours but remarks at the opening for 2 hours. In this study, the authors used a descriptive qualitative research method, which provides an overview of the problem under study, which is related to the implementation of empowerment. The results showed that the implementation of empowerment for underprivileged women by PKK cadres carried out in Bingkeng Village, Dayeuhluhur District, Cilacap Regency based on the empowerment implementation strategy was not optimal. The obstacles that arise are the lack of interest of women in the program, the funds provided from the Village Fund are not sufficient for the program needs, the distance to the training center, namely the Village Hall, is quite far and the quality of human resources for PKK cadres and women is still low. Efforts to overcome obstacles that arise are implementing approaches to women by providing motivation, applying for additional funds to village officials for the smooth running of the program, providing vehicle inventories for participants who do not have vehicles, and holding special training for PKK cadres.